HELICOTYLENCHUS SPECIES ASSOCIATED WITH CAJANUS CAJAN (L.) MILLSP. WITH A DESCRIPTION OF A NEW SPECIES FROM MANIPUR - TH. TARNITA; R. K. GAMBHIR; L. BINA (The Bioscan, 2012)
A survey of soil nematodes associated with Cajanus cajan (L.) Millsp. from different localities of Manipur revealed the presence of abundant of Helicotylenchus species. The present study reveals a new species of Helicotylenchus. Helicotylenchus constrictus sp. nov. was characterised by having 618.24μm long body, a =24, b= 5.18, b’= 4.26, c = 34.9, v= 62.76 and Stylet = 20.93.